Pengaruh Pembelajaran Matematika dengan Strategi Group Investigation dan Realistic Mathematics Education Ditinjau dari Tingkat Kemandirian Belajar Siswa (Pada Siswa Kelas X SMK 1 Muhammadiyah Sukoharjo Tahun Ajaran 2013/2104) - Mustaqim, Galang, Dra. Sri Sutarni, M.Pd (2015)
This study aimed to analyze: (1) the effect of the strategy GI RME learning and the learning outcomes of mathematics, (2) learning independence influence on mathematics learning outcomes, and (3) interaction between the learning strategies and learning independence against mathematics learning outcomes. This type of research, experimentation. population This research was all students of class X SMK Muhammadiyah 1 Sukoharjo Academic Year 2013/2014. A sample of two classes: The treated experimental class learning strategies GI, and control class treated RME learning strategy. Technique Sampling was done by using Cluster Random Sampling. Data collection methods used were test and questionnaire as the principal methods and documentation as an auxiliary method. The analysis technique in this research is the analysis of variance of two different cell, previously performed the prerequisite test is test normality and homogeneity test. Based on the research results = 5%, obtained: (1) There is influence between RME and GI strategy against the results of students' mathematics learning, (2) There is an effect between independence learning students' mathematics learning outcomes, and (3) None interaction between the learning strategies and student learning independence the learning outcomes of mathematics